Aplikasi Sistem Informasi Geografis Dalam Pemetaan Zonasi Rawan Banjir Kecamatan Monano Kabupaten Gorontalo Utara - Agustaman, Rukmini; Kasim, Muhammad; Hutagalung, Ronal (Journal of Applied Geoscience and Engineering, 2022)
Monano Subdistrict is one of the sub-districts located in Gorontalo UtaraRegency, Gorontalo Province, which does not have a flood hazard map. Thisstudy aims to determine the geological conditions and create a flood hazardmap. This study collected field data, such as lithological data, plotting dataon flood coordinates of each village, as well as validation data of the floodhazard level. The spatial analysis used in this research scores on flood-proneparameters, such as slope, rainfall, and land use that are overlayed alongwith lithological data. As a result, four geomorphological units are obtained:volcanic hills, denudational hilss, and fluvial and marine plains. From thegeological aspect, four units of lithology constituents are produced, such asandesite units, agglomerate units, sandstone units, and alluvial deposit units.The data also exposes that: slopes range from 0-45o flat to very steep, landuse is covered by settlements, rice fields, shrubs, and forests, as well asrainfall which refers to a very high intensity of rainfall, which is 2771 mmper year. The data obtained produces a flood hazard map divided into threeclasses: low, medium, and high.